Body appreciation and motivation toward physical activity as predictors of eating habits in university students from the Peruvian Altiplano - Marisol Yana-Salluca; Edwin Gustavo Estrada-Araoz; Nancy Yana-Salluca; Reynaldo Cutipa-Luque; Zara Turpo-Puma; Gilber Chura-Quispe; Elizabeth Orfelia Cruz-Laricano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and objective: during the university stage, eating habits may deteriorate due to factors such as increased academic responsibilities, greater autonomy in decision-making, and changes in daily routines. In the Peruvian highlands, these conditions are exacerbated by sociocultural and economic limitations, making it relevant to investigate the psychological factors that influence the eating behaviors of this population. The objective of the present study was to determine whether body appreciation and motivation toward physical activity predict eating habits among university students in the Peruvian highlands.